Reflection on Nursing care from the point of view of human spirituality and a Christian attitude: DOI: 10.15343/0104-7809.200933.2.10 - de Sá, Ana Cristina (2009)
Spirituality is a subject that health professionals are increasing considering to care for human beings, due to the fact thatrecent research are showing that this can be a way to improve the quality of life of patients, as well as accelerating the cure processand/or combating diseases. Besides, the attitudes described of Jesus Christ before sick people as described in the Bible are very similarto what today one calls humanization of health services, besides stimulating self-care (“your faith has cured you”) and the shelter ofthose excluded by society, placing such acts as sufficiently appropriate paradigms for those who choose nursing as a profession that hascaring of human beings as its study subject. This work aims to place spirituality and Jesus attitudes as paradigms for nursing work. Abibliographical survey was done in the databases BDENF, LILACS, BIREME and MEDLINE, besides an active search in specialized librariesof other sources such as books, dissertations and doctorate theses. One concludes that the surveyed literature tends to confirm theproposal of spirituality and Jesus Christ attitudes as parameters that seem to address yearnings of patients regarding the quality andhumanization in the assistance to vital human necessities. However, the training offered and the curriculums of courses in the Healtharea seem neither to emphasize nor to prepare future professional for this practice.